MULTI-TEMPORAL ANALYSES OF LAND COVER AND USE IN THE CITY OF UNISTALDA, RS - Vasconcellos, Bruna Nascimento de; Terra, Lueni Gonçalves; Cardoso, Claire Delfini Viana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
In the last decades, a disorganized process of land occupationhas been observed, due mainly to urban growth and population density. In this sense, studies that aim to understand the dynamics of these occupations in different areas, so that planning policies are effective, are imperative. Given this, the present study has as objective to analyze the temporal dynamics of land use and occupation in the city of Unistalda – RS, since its independence in 1995. Thematic maps of the years 1995, 2000 and 2010 were made from the satellite Landsat 5’s images. For the accomplishment of this work, images were downloaded and imported. From that, georeferencing has been done, as well as the digital processing, the recognition of use patterns and then the supervised digital classification. The mappings allow the verificationof the landscape alterations in the periodstudied. Forest, field and bare ground classes varied in a non-linear way,whileagriculture and forestry classes showed a growing pattern since 1995.